Landscape structure in Bahia, Brazil: an analysis from the Gini index - Andrade Santos, Sara; da Silva Gomes, Andréa; de Moura Pires, Mônica; Lima Gomes , Ronaldo (Sociedade & Natureza, 2020)
The phenomenon of high level of land concentration may be explained mostly by a country's agrarian history. The ownership and usage of land in Brazil and Bahia reveal the antagonism caused by a relationship of subordination, expropriation and exploitation between a dominant social class represented by landowners and peasants, a setting which encourages a contextualized analysis of the current Brazilian landed structure. In this context, this paper analyzes Bahia's current landed structure, by applying the Gini index (GI) for the land and the spatial group technique (clusters), in the census years of 2006 and 2017 for the 417 municipalities in Bahia. On the report of results obtained by GI and used ranking, it was identified a significant land concentration in Bahia, albeit there was a moderate reduction between 2006 and 2017. According to the spatial analysis, there is a gathering with high concentration, especially in the municipalities from the Região Geográfica Intermediária de Barreiras (a Brazilian term for a geographical division used by the Instituto Brasileiro de Geografia e Estatística – IBGE), while there is a cluster of municipalities with low GI values within the Região Geográfica Intermediária de Guanambi and also in Vitória da Conquista’s one. The analysis reveals the existence of a correlation between landed structure and socioeconomic aspects from the regions.